POSITIONING OF WHEAT CULTIVARS AND THEIR RELATION WITH THE NUTRITIONAL QUALITY OF GRAINS - Willyan Júnior Adorian Bandeira; Ivan Ricardo Carvalho; Murilo Vieira Loro; Leonardo Cesar Pradebon; João Pedro Dalla Roza; Jaqueline Piesanti Sangiovo; Kassiana Kehl (Revista de Agricultura Neotropical)
The objective of this study was to select wheat genotypes with potential to improve grain nutritional quality. An experiment was conducted in 10 environments in the state of Rio Grande do Sul, Brazil. Five wheat genotypes were sown (BRS Parrudo, LG ORO, Mirante, ORS 1403, and TBIO Sinuelo), using a randomized block experimental design with two replications. Grain crude protein, lipid, crude fiber, mineral matter, and non-structural carbohydrate contents were evaluated. The data were subjected to analysis of variance and Tukey's test at a 5% significance level. The method proposed by Annicchiarico and the additive main effects and multiplicative interaction (AMMI) model were used to analyze the adaptability and stability of the genotypes. The genotype LG ORO was identified as the agronomic and nutritional ideotype, demonstrating stability and superiority in crude proteins, lipids, and non-structural carbohydrates in grains.